Industrial relations in the new workplace: research, policy and practice - Giles, Anthony; Lapointe, Paul-André; Murray, Gregor; Bélanger, Jacques (Relations industrielles / Industrial Relations, 1999)
Introduces the international colloquium co-sponsored by Laval University's Industrial Relations Centre and the Canadian Workplace Research Network held in September 1997.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; R&D; Research; Research & development; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z